Motivation Mechanism Prevents Adverse Selection in Industrial Technology Innovation Strategic Alliance. (7th July 2014) - Zhao, Mingxia; Li, Changhong
Abstract : Choosing proper partners is the key to the success of the alliance. Based on the analysis of the characters of the Industrial Technology Innovation Strategic Alliance, a new kind of cooperative organization occurred in China in recent years. The problem of "adverse selection" at the stage of the its establishment is discussed in this paper. The game model is built based on motivation theory and the principle-agent theory and then proved by examples. The conclusions can be got from the model. By setting the ranges of funds, preferential policy, and sharable profits and designing membership rules, the organizer of the Industrial Technology Innovation Strategic Alliance can motivate the risk neutral applicant to reveal his real capacity and the one with higher capacity to participate intothe alliance more actively and even can set capacity threshold for applicants implicitly.